Ironclad US commitment to NATO? From NATO expansion to the Ukraine crisis - Yanan Song (Cogent Social Sciences, 2024)
Russia’s invasion of Ukraine in 2022 is not an accident but an inevitable consequence of how the West, especially the US, has utilised NATO in the post-Cold War period. This encompasses the activities which the US has supported NATO to pursue in the last 30 years: transformation, expansion, and participation in “out of area” actions. However, the US has never found it easy to help NATO remain the leading security organisation in Europe, not only because of threats posed by outside actors like Russia but also the mounting internal challenges, especially the long-standing issue of a “two-tiered” alliance. Washington has already shown reluctance to utilise NATO in Afghanistan, Libya, Syria, and now Ukraine to varying degrees. This paper seeks to understand why the US has remained committed to NATO and how the future US-NATO relationship will likely fare, including whether the Ukraine crisis can inject new life into the Alliance. It is believed that in the current context of uncertainty posed by NATO’s “Smart Defence” and the US “Pivot to Asia”, it seems highly likely that unless something changes, NATO will end up just doing less with less.